Apoptotic abscess imaging with 99mTc-HYNIC-rh-Annexin-V - Penn, David L.; Kim, Christopher; Zhang, Kaijun; Mukherjee, Archana; Devakumar, Devadhas; Jungkind, Donald; Thakur, Mathew L. (Nuclear medicine and biology, 2010)
Abscess formation causes systemic and localized up-regulation of neutrophil [polymorphonuclear leukocytes (PMNs)] signaling pathways. In the abscess, following bacterial ingestion or PMN activation by inflammatory mediators, PMN apoptosis is elevated and leads to the externalization of phosphatidylserine. Annexin-V (AnxV) has been shown to have high affinity to externalized phosphatidylserine. We hypothesized that 99mTc-AnxV will target high densities of apoptotic PMNs and image abscesses. AnxV, conjugated with hydrazinenicaotinamide (HYNIC), was labeled with reduced 99mTcO 4 − and its purity was determined by instant thin-layer chromatography. Apoptosis was induced in isolated human PMNs by incubation in 2% saline for 17 and 22 h at 37°C. PMNs were then incubated with 99mTc-HYNIC-AnxV and associated 99mTc was determined. Abscesses were induced in mice by intramuscular injection of bacteria or turpentine. Following intravenous administration of 99mTc-HYNIC-AnxV, mice were imaged and tissue distribution studied at 4 and 24 h. Radiochemical purity of 99mTc-HYNIC-AnxV was 84.9±8.11%. At 17 h, 99mTc-HYNIC-AnxV bound to apoptotic PMNs was 71.6±0.01% and 48.6±0.01% for experimental and control cells, respectively ( P=.002). At 22 h, experimental cells retained 74.9±0.02% and control cells retained 47.2±0.02% ( P=.005). 99mTc-HYNIC-AnxV associated with bacterial abscesses was 1.25±0.09 and 3.75±0.83 percent injected dose per gram (%ID/g) at 4 and 24 h compared to turpentine abscesses which was 1.02±0.16 and 0.72±0.17 %ID/g at 4 ( P≤.05) and 24 h ( P≤.01). 99mTc-HYNIC-AnxV represents a minimally invasive and promising agent to image and potentially distinguish between infectious and inflammatory abscesses.